Genomic analysis of inbreeding level, kinship and breed relationships in Creole cattle from South America - Marcuzzi, Olivia; Calcaterra, Francisco; Loza Vega, Ariel Jhonny; Ortega Masague, Maria Florencia; Armstrong, Eileen; Pereira Rico, Juan A.; Jara Tellechea, Eugenio Salvador; Olivera, L. Hernán; Peral Garcia, Pilar; Giovambattista, Guillermo (Wiley, 2025)
The conservation of animal genetic resources refers to measures taken to prevent the loss of genetic diversity in livestock populations, including the protection of breeds from extinction. Creole cattle populations have suffered a drastic reduction in recent decades owing to absorbent crosses or replacement with commercial breeds of European or Indian origin. Genetic characterization can serve as a source of information for conservation strategies to maintain genetic variation. The objective of this work was to evaluate the levels of inbreeding and kinship through the use of genomic information. A total of 903 DNAs from 13 cattle populations from Argentina, Bolivia and Uruguay were genotyped using an SNP panel of 48 K. Also, a dataset of 76 K SNPs from Peruvian Creole was included. Two inbreeding indices (FROH and Fhat2) and kinship relationships were calculated. In addition, effective population size (Ne), linkage disequilibrium, population composition and phylogenetic relationships were estimated. In Creole cattle, FROH ranged from 0.14 to 0.03, and Fhat2 was close to zero. The inferred Ne trends exhibited a decline toward the present for all populations, whereas Creole cattle presented a lower magnitude of Ne than foreign breeds. Cluster analysis clearly differentiated the taurine and Zebu components (K2) and showed that Bolivian Creole cattle presented Zebu gene introgression. Despite the population reduction, Creole populations did not present extreme values of consanguinity and kinship and maintain high levels of genetic diversity. The information obtained in this work may be useful for planning conservation programmes for these valuable local animal genetic resources.